A review of optical flow models applied for fluid motion estimation - Osman, A.B. (Asian Research Publishing Network, 2016)
Fluid flow estimation from image sequences is a challenging due to the large and complex nature of fluid flow. In this work, 36 papers on optical flow models applied for fluid motion estimation from 1980 to 2015 have been reviewed. The advantages and weaknesses of the optical flow models are discussed in detail. To improve the accuracy of the optical flow models, the principle of two multi-resolution schemes is discussed. The employment of higher order models provides more accurate motion vectors than the use of the standard optical flow model; however, it suffers from computational complexity. The use of the multi-resolution framework such as wavelet decomposition will reduce this complexity, as well as improve estimation accuracy. Â©2006-2016 Asian Research Publishing Network (ARPN).